A Comparative Study of Health Utility Value and in Type 2 Diabetes Mellitus Patients Treated With Oral Monotherapy or In Combination with Oral or Insulin (Jurnal Farmasi Udayana, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic disease with a high clinical and economic burden. This study aimed to compare health utility values and costs among T2DM patients receiving different therapeutic regimens, including oral monotherapy, oral combination therapy, insulin monotherapy, insulin combination therapy, and oral–insulin combination therapy. This study used an analytical observational design with a cross-sectional approach involving 119 patients. Data were collected using a structured questionnaire for patient characteristics and the EQ-5D-5L instrument to assess utility values, while cost analysis was conducted from the patient perspective, including direct and indirect costs. The results showed that oral monotherapy had the highest utility value (QALY 23.89) and a cost of Rp406.941,25 per patient/month, making it the most cost-effective therapy. In contrast, insulin-based therapies tended to have higher costs and lower utility values. Cost variations were observed across all components, with the highest drug costs found in insulin monotherapy. In conclusion, oral therapy, particularly monotherapy, represents the most economically and clinically efficient option. Early intervention and optimal disease management are essential to prevent disease progression and reduce long-term economic burden.